Lightweight, flexible and superhydrophobic composite nanofiber films inspired by nacre for highly electromagnetic interference shielding. (January 2020) - Li, Ting-Ting; Wang, Yanting; Peng, Hao-Kai; Zhang, Xuefei; Shiu, Bing-Chiuan; Lin, Jia-Horng; Lou, Ching-Wen
Abstract: Inspired by the hierarchical structure of nacre, this study prepared a lightweight, flexible, and superhydrophobic polyacrylonitrile (PAN)@SiO2 -Ag composite nanofibrous film with high performance electromagnetic-interference shielding via electrospinning. SiO2 incorporated into PAN electro-spun films provided the adhesion site for Ag nanoparticles (AgNPS ). AgNPS were then deposited onto the surface of PAN@SiO2 electrospinning nanofibers via facile wet electroless deposition, thus endowing the resulting nanofibers with a core–shell structure. After finishing with a PTDT agent, PAN@SiO2 -Ag composite nanofiber films had super hydrophobic property, and their water contact angle reached 156.99°. This scenario also presented high conductivity (approximately 17, 788 S/m), average shielding effectiveness (SE), specific SE (SSE), and SSE/t, achieving 82 dB, 367 dB cm 3 g −1 and 73, 478 dB cm 2 g −1, respectively. This study provides an easy method to prepare bioinspired composite films with high conductive and electromagnetic shielding and high potential applications, such as in wearable and flexible sensors.